Epidemiological features of travel-related cases Mpox (Monkeypox) cases detected at airports in Pakistan; Insights from Screening Surveillance - Dr Nadia Noreen (International Journal of Infectious Diseases)
Background: The 2022 multi-country outbreak of Monkeypox virus (Mpox) was declared as PHEIC. Pakistan reported five human Mpox cases in travelers returning to Pakistan filtered at the points of entry (airports) through entry screening. This study was done to analyze the descriptive epidemiology of imported Mpox passengers detected at the points of entry (airports) across Pakistan. Methods: It was a descriptive study conducted at the Directorate of Border Health Services (DOBHS) the focal point of all the points of entry in Pakistan from 20th April 2023 to 12th May 2023. The surveillance data of the confirmed Mpox cases in Pakistan was abstracted from the traveler's surveillance management information system maintained by DOBHS. Contact tracing of contacts at airports and healthcare settings was undertaken. Data analysis was done as descriptive statistics as percentages and frequencies using Epi info version 7 and SPSS version 24. Results: The five reported cases were between 19 and 50 years with a mean age of 32.5± 13.11 years. The male-to-female ratio was 4:1. All cases had a travel history linked to Saudi Arabia. All cases were confirmed through PCR. They presented with skin lesions (100 %), fever (80 %), and lymphadenopathy (60 %). The illness was mild to moderate with the mean duration of skin rash 7-10 days. The contact tracing revealed no secondary cases of Mpox in the community or the healthcare setting. Discussion: The descriptive epidemiology of imported Monkeypox virus (Mpox) cases detected at points of entry (airports) in Pakistan highlights the critical role of effective screening and surveillance systems in controlling disease spread. The analysis revealed a clear association between travel to Saudi Arabia and Mpox cases, indicating a likely source of exposure. Prompt identification of cases through PCR testing enabled timely intervention and containment measures. Although presenting with typical symptoms such as skin lesions, fever, and lymphadenopathy, the illness remained mild to moderate in severity, with no secondary cases detected through contact tracing efforts. These findings emphasize the importance of robust screening protocols and the need for trained personnel to recognize and manage potential Mpox cases at points of entry. Early detection facilitates prompt isolation, medical care, and contact tracing, ultimately mitigating the risk of onward transmission and effectively containing Mpox outbreaks. Conclusion: All cases had a travel history associated with Saudi Arabia, indicating a likely source of exposure. The findings underscore the significance of effective screening protocols and the role of trained personnel in identifying and managing potential monkeypox cases at points of entry. Early detection enables prompt isolation, appropriate medical care, and contact tracing, thereby reducing the risk of onward community transmission and containment of monkeypox cases.